Akses dan Pembagian Manfaat di dalam Draft Akademik Rancangan Undang-Undang Pengelolaan Sumber Daya Genetika - Yulia, Yulia (Jurnal Ilmu Hukum Reusam, 2015)
Access and benefits sharing is one principle in the Convention on Biological Diversity (CBD) and reaffirmed in Nagoya Protocol. The principle has supported to provider countries of biodiversity to getting benefits sharing of used biodiversity by industries. Therefore, its to getting benefits sharing which fair and balanced, provider countries require specific regulation. Draf Akademik Rancangan Undang-undang Pengelolaan Sumber Daya Genetika (Academic Draft of RUU) is realization require of Indonesia to getting benefits sharing. This article has founds are Academic Draft of RUU the Genetic Resources Management has corresponded with CBD and Nagoya Protocol. Although, there are any points that are not clear, as like the scope of biodiversity and usage.